Angioplastía coronaria en pacientes octogenarios - Ugalde P., Héctor Ugalde P.; Pizarro J., Gonzalo; Dreyse O., Ximena; Espinosa O., Pilar (Revista Hospital Clínico Universidad de Chile, 2007)
Introduction: According to international literature, the percutaneus coronary angioplasty (PTCA) can be performed in octogenarian with a high rate of success and favorable long term prognosis. There are no Chilean publications about PTCA in octogenarian patients. Objective: To show our experience in octogenarian patients who underwent PTCA. Material and method: From a serial prospective registration of patients who underwent coronary angiography studies between 1992 and 2005, all the octogenarian patients subjected to PTCA were evaluated, being described their pre and in-hospital variables, with emphasis in the results of the PTCA Results: Of a total of 7262 patients, 77 octogenarian patients underwent PTCA (1%). The average age was 83.2 ± 3.4 years, 54.5% male. They were studied mainly by myocardial infraction (MI) (55.8%) and unstable angina (29.8%). 59.7% were hypertensive and 19.4% had diabetes. The angiographic study showed mainly single vessel (37.6%) and two vessel disease in 32.4%. The PTCA was elective in 57.1%, the rest were emergency procedures. The PTCA was successful in 88.3%. There were no intra procedure complications, and 7 patients presented smaller post procedure complications. 11 patients (14.3%) died; 10 because of MI. 66 were discharged without complications. Conclusion: The PTCA is a feasible procedure to perform in octogenarian patients, with good immediate results.